Children's and Families' Holiday Experience. - Carr, Neil (Taylor & Francis, 2011)
Children's and Families' Holiday Experience is the first volume to consider the active social role of children (0 - 18) as well as parents in shaping the nature of the family holiday experience. It provides significant insights into the holiday desires, expectations, and experiences of children and the families' tourism behaviour, that offers the potential for the tourism industry to plan, develop, and market products that provide a higher quality service to these populations. This book traces the modern history of the demand for and provision of holidays for children and families. As part of.